2013
DOI: 10.1056/nejmsa1300237
|View full text |Cite
|
Sign up to set email alerts
|

Publication of Trials Funded by the National Heart, Lung, and Blood Institute

Abstract: BACKGROUND Rapid publication of clinical trials is essential in order for the findings to yield maximal benefits for public health and scientific progress. Factors affecting the speed of publication of the main results of government-funded trials have not been well characterized. METHODS We analyzed 244 extramural randomized clinical trials of cardiovascular interventions that were supported by the National Heart, Lung, and Blood Institute (NHLBI). We selected trials for which data collection had been comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 10 publications
8
89
0
Order By: Relevance
“…8 Similarly, an analysis of 244 extramural clinical trials supported by the National Heart, Lung, and Blood Institute and completed between 1 January 2000 and 31 December 2011 found that 43% of clinical trials remained unpublished within 30 months. 16 Our analysis extends previous work by reporting publication rates across leading academic institutions and shows a nearly twofold variation in the rate of publication overall and a more than threefold variation in the rate of publication within 24 months. With regard to reporting of results on ClinicalTrials.…”
Section: Discussionsupporting
confidence: 71%
“…8 Similarly, an analysis of 244 extramural clinical trials supported by the National Heart, Lung, and Blood Institute and completed between 1 January 2000 and 31 December 2011 found that 43% of clinical trials remained unpublished within 30 months. 16 Our analysis extends previous work by reporting publication rates across leading academic institutions and shows a nearly twofold variation in the rate of publication overall and a more than threefold variation in the rate of publication within 24 months. With regard to reporting of results on ClinicalTrials.…”
Section: Discussionsupporting
confidence: 71%
“…These numbers may be considered as optimistic, because we excluded studies that had enrolled patients but discontinued before study completion. Two recent evaluations with study designs similar to ours assessed time to publication among registered clinical trials funded by the NIH (17 ) and the National Heart, Lung, and Blood Institute (18 ). Respectively 46% (294/635) and 57% (132/244) of the trials had been published within 30 months of completion, which is comparable to the 45% rate found in our study.…”
Section: Discussionsupporting
confidence: 83%
“…These issues can only be addressed properly in prospective randomized trials. 30,31 However, in current transplant practice, randomized trials are performed infrequently due to both the relatively small numbers of patients affected and to patient and physician treatment preferences. 32 This lack of randomized trials necessitates alternative analysis methods, in which as many insights as possible are extracted from observational data.…”
Section: Discussionmentioning
confidence: 99%